1999
DOI: 10.1098/rspb.1999.0914
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the relative fitness of local adaptive peaks: the aerodynamic costs of flight in mimetic passion–vine butterfliesHeliconius

Abstract: In a related paper, we demonstrated that mimetic Heliconius butter£ies have converged in wing-beat frequency and degree of asymmetry in the wing motion, whereas sister species are dissimilar in these same traits. Warning signals of sympatric, distasteful species converge in evolutionary models in order to educate their predators more e¤ciently that the signal is associated with unpro¢table prey. Barring other constraints, the behaviours of the di¡erent co-mimetic pairs should ultimately converge on that behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…However, morphological convergence in mimics may also result in wingbeat frequency convergence for reasons of aerodynamic force production (Srygley 1999). The higher wing-beat frequencies of the melpomene^erato group require greater aerodynamic power and thus they are energetically more costly than the relatively low wing-beat frequencies in the cydno^sapho group (Srygley & Ellington 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, morphological convergence in mimics may also result in wingbeat frequency convergence for reasons of aerodynamic force production (Srygley 1999). The higher wing-beat frequencies of the melpomene^erato group require greater aerodynamic power and thus they are energetically more costly than the relatively low wing-beat frequencies in the cydno^sapho group (Srygley & Ellington 1999).…”
Section: Discussionmentioning
confidence: 99%
“… References: 1, Dixon & Kindlmann (1999); 2, Denno et al (1985); 3, Kisimoto (1956); 4, Dixon et al (1993); 5: Ahlroth et al (1999); 6, Fjerdingstad et al (2007); 7, Yano & Takafuji (2002); 8, Xiao et al (2007); 9, Ostergard et al (2007); 10, Greig (1993); 11, Traveset (1991); 12, Zagt (1997); 13, Fedriani & Manzaneda (2005); 14, Grimm (1995); 15, Silva & Taberelli (2001); 16, Young & Lockley (1988); 17, Bell et al (2005); 18, Cummings et al 1993); 19, Deblok & Tanmaas (1977); 20, Lundquist et al (2004); 21, Oliver & Retiere (2006); 22, Craig (1997); 23, Vahl & Clausen (1980); 24, Cheung et al (2006); 25, Vander Wall & Longland (2004); 26, Allen & McAlister (2007); 27, Hiddink et al (2002); 28, Hiddink & Wolff (2002); 29, Pechenik (1999); 30, Aukema & Raffa (2004); 31, Korb & Linsenmair (2002); 32, Srygley (2004); 33, Galeotti & Inglisa (2001); 34, Amo et al (2007); 35, Bonnet et al (1999); 36, Hamann et al (2007); 37, Jessop et al (2004); 38, Pietrek et al (2009); 39, Winne & Hopkins (2006); 40, Smallwood et al (2009); 41, Real & Manosa (2001); 42, Massemin et al (1998); 43, Kenward et al (1999); 44, Solomon (2003); 45, Soulsbury et al (2008); 46, Adamo et al (2008); 47, Srygley et al (2009); 48, Adamo & Parsons (2006); 49, Calleri et al (2006); 50, Bennet & Marshall (2005); 51, Crawford (1992); 52, Epp & Lewis (1984); 53, McHenry & Patek (2004); 54, Wendt (2000); 55, Combes & Dudley (2009); 56, Berrigan (1991); 57, Hedenstrom et al (2001); 58, Srygley & Ellington (1999); 59, Kram (1996); 60, Kramer & McLaughlin (2001); 61, Berrigan & Lighton (1994); 62, Full & Tullis (1990); 63, Duncan & Crewe (1993)…”
Section: Organisation Of Dispersal Costsmentioning
confidence: 99%
“…Studies of Heliconius and other butterflies have previously demonstrated that locomotor mimicry may be achieved by kinematic (Srygley ; Srygley and Ellington ), aerodynamic (Srygley and Ellington ), and morphological effects (Srygley ). However, Srygley () found no evidence of convergence of wing shape between comimics, and suggested that this may be due to (i) conflicting selective forces operating on the wing; (ii) the evolution of dark apical margins contrasting against the bright colors of the wing, which can create false outlines to the wing that closely resemble those of the model species; (iii) a lack of sufficient selection pressure; or (iv) relatively imprecise measurements of wing shape.…”
Section: Discussionmentioning
confidence: 99%
“…Batesian mimics, which are not chemically defended, are also known to fly slowly and deliberately, so accurately resemble their model species in both their display patterns and locomotory behavior, but retain the wide thoraces and powerful flight muscles from their ancestry, allowing them to adopt more rapid and erratic flight behaviors when pursued by a predator (Chai and Srygley 1990;Srygley 1994Srygley , 2004. Srygley and Ellington (1999a) described a more subtle aspect of mimetic flight behavior in Müllerian mimic species: both wing-beat frequency and wing motion symmetry could be used to discriminate the comimics H. cydno and H. sapho from a second comimicry group, H. melpomene and H. erato. Although convergence on similar wing-beat frequencies may be related to requirements of aerodynamic force, variation from nearly sinusoidal to more asymmetrical wing motions is expected to have little effect on lift production.…”
Section: Ecological Significancementioning
confidence: 99%
See 1 more Smart Citation